Market Accessibility and Regional Maps : Kyrgyz Republic - Blankespoor, Brian (World Bank, Washington, DC, 2014)
Access to markets is argued to have a significant role in development. In order to quantify the access of places to markets, policy makers are showing increasing interest in accessibility indicators (Yoshida and Deichmann 2009). This paper seeks to examine the spatial relationship of access to market in the Kyrgyz Republic using a recent census and household survey in order to identify possible linkages with rates of poverty and other micro (spatial) information. This analysis uses the market accessibility index that measures the potential connectivity of population or expenditures between village/towns and big cities via the transport network. Results show that high market accessibility is located near the large cities with a concentration of infrastructure, while low access is more in the rural areas. Future work will use this indicator in economic models to statistical identify its significance with regards to per capita expenditure and poverty.